Analisis Tingkat Kedisiplinan Peserta Didik terhadap Tata Tertib di Sekolah Dasar Kota Bukittinggi - Mai Sri Lena; Sartono Sartono; M. Tegar Fadillah; Zul Afwan (Universitas Pahlawan Tuanku Tambusai, 2023)
Discipline is one of the most crucial things for every student and must be developed since elementary school as a social attitude that becomes an example for the next generation. In this case, every student in elementary school must have discipline character towards the code of conduct in their elementary school. This study is researched to find out how the level of discipline of the students in elementary school. This will also find out about how student attitude towards the code of conduct. This study is using quantitative descriptive with survey method. Study method that will be used for this study is questionnaire with google form as the technique to gain the data. Keywords: discipline, elementary school, code of conduct